2020
DOI: 10.1128/mbio.02243-20
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired Cytotoxic CD8+T Cell Response in Elderly COVID-19 Patients

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection induces a T cell response that most likely contributes to virus control in COVID-19 patients but may also induce immunopathology. Until now, the cytotoxic T cell response has not been very well characterized in COVID-19 patients. Here, we analyzed the differentiation and cytotoxic profile of T cells in 30 cases of mild COVID-19 during acute infection. SARS-CoV-2 infection induced a cytotoxic response of CD8+ T cells, but not CD4+ T cells, c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
95
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 39 publications
12
95
0
2
Order By: Relevance
“…Gong F. et al [34] have also shown that SARS-CoV-2-specific CD8+ T-cells typically had a more effector phenotype. Westmeier, J. et al [36] found that SARS-CoV-2 infection induced a cytotoxic response of CD8+ T cells, characterized by the simultaneous production of granzyme A and B as well as perforin. Moreover, they indicated that CD8+ cells were not functionally exhausted.…”
Section: T Cells Maturation In Covid-19 Patients: Role Of Central Memmentioning
confidence: 99%
“…Gong F. et al [34] have also shown that SARS-CoV-2-specific CD8+ T-cells typically had a more effector phenotype. Westmeier, J. et al [36] found that SARS-CoV-2 infection induced a cytotoxic response of CD8+ T cells, characterized by the simultaneous production of granzyme A and B as well as perforin. Moreover, they indicated that CD8+ cells were not functionally exhausted.…”
Section: T Cells Maturation In Covid-19 Patients: Role Of Central Memmentioning
confidence: 99%
“…4 Elderly COVID-19 patients have impaired Cytotoxic CD8 + T Cell Responses, which may make them highly risk for infection. 5 A. baumannii is a common pathogen in Intensive Care Units (ICU) and evolves rapidly to be resistant to many antibiotics and should be seriously considered for critical COVID-19 patients. 6 In summary, we carried out an extensive pathogen screening in a COVID-19 cohort.…”
mentioning
confidence: 99%
“…However, the CD8+ T cells of the elderly group (ages 80–96) did not upregulate the cytotoxic markers Granzyme B and Perforin as the younger group did (ages 29–79), indicating age-related exhaustion ( 15 ). They conclude PD-1 expressing CD8+ cells should not be ‘misclassified’ as exhausted, however they state that PD-1 therapy may improve virus control (presumably in the elderly group) but also may “exaggerate the immunopathology in the lungs and other organs” ( 15 ). We agree with this therapy in regard to aged patients but also propose that cytotoxic function may be overexuberant in younger populations and that withholding differentiation may, to an extent, temper Granzyme and Perforin expression.…”
Section: Discussionmentioning
confidence: 95%
“…Zheng et al did not find lymphopenia in their cohort, however they noted that a non-exhausted subgroup of PD-1- CTLA4- TIGIT- CD8+ T cells were significantly reduced in percentage in patients with severe Covid-19 compared to mild and moderate ( 14 ). Westmeier et al sought to characterize the proteins that cause cytotoxicity and possibly immunopathological organ damage, and they found in young (29–79) patients CD8+ T cells activated ex vivo following convalescence produced granzymes A, B, and perforin at greater levels than healthy donors despite expressing PD-1, suggesting the exhaustion was not functional despite PD-1 expression ( 15 ). However, the CD8+ T cells of the elderly group (ages 80–96) did not upregulate the cytotoxic markers Granzyme B and Perforin as the younger group did (ages 29–79), indicating age-related exhaustion ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation